2013
DOI: 10.1007/s00125-013-2975-0
|View full text |Cite|
|
Sign up to set email alerts
|

Non-attendance at diabetic eye screening and risk of sight-threatening diabetic retinopathy: a population-based cohort study

Abstract: Aims/hypothesis This study evaluated whether repeated nonattendance for diabetic eye screening is associated with the risk of sight-threatening diabetic retinopathy (STDR). Methods This was a cohort study of 6,556 residents with diabetes who were invited for screening between 2008 and 2011 in a population-based eye screening programme in inner London and who attended for their first-ever screen in 2008. The proportion of participants with STDR was evaluated in relation to the number of years in which screening… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
39
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 19 publications
5
39
0
1
Order By: Relevance
“…Therefore, screening for diabetes may lead to the detection of retinopathy at an earlier stage before clinically evident complications occur. In line with this, it has been shown that patients who do not attend diabetic eye screenings are at increased risk of developing sight-threatening diabetic retinopathy [12].…”
Section: Introductionmentioning
confidence: 79%
“…Therefore, screening for diabetes may lead to the detection of retinopathy at an earlier stage before clinically evident complications occur. In line with this, it has been shown that patients who do not attend diabetic eye screenings are at increased risk of developing sight-threatening diabetic retinopathy [12].…”
Section: Introductionmentioning
confidence: 79%
“…Diabetic retinopathy (DR) is a major cause of vision loss, globally , and disproportionately affects vulnerable populations, such as those in low‐income countries and Indigenous populations . DR screening has been widely promoted for decades; however, adherence to recommendations remains suboptimal, particularly among those at higher risk of DR and vision loss .…”
Section: Introductionmentioning
confidence: 99%
“…Failure to attend outpatient appointments is a particularly prevalent issue in the diabetic population and is associated with poorer outcomes [38, 39]. Of the 54 patients referred by our eye department to the diabetic retinopathy clinic, 22 failed to attend their initial clinic appointment.…”
Section: Discussionmentioning
confidence: 99%